Eksperimentasi Model Pembelajaran Team Accelerated Instruction (TAI) Dan Two Stay Two Stray (TSTS) Terhadap Prestasi Belajar Ditinjau Dari Motivasi Belajar Pada Siswa MTs Negeri Karangmojo Kelas VII Semester 2 Tahun Ajaran 2015/2016 - Primantika, Selly Wieldya Trias, Drs. Slamet H.W, M.Pd (2016)
The aim of research to finding out and analyzing: (1) The effect of Team Accelerated Instruction (TAI) learning model and Two Stay Two Stray (TSTS) learning model towards mathematics learning achievement, (2) The effect of learning motivation of students towards mathematics learning achievement, (3) The interaction between Team Accelerated Instruction (TAI) learning model and Two Stay Two Stray (TSTS) learning model viewed from learning motivation of students towards mathematics learning achievement. The type of the research is experiment with quasi experimental design. The population of the research was all students of VII Grade of MTs Negeri Karangmojo of entire semester of academic year 2015/2016. The research sample are two classes. consisting of 32 students as an experimental class and 33 students as the control class. The sampling technique use cluster random sampling. Methods of data collection use test, questionnaires and documentation. Data analyzed by analysis of variance with two different cell lines. The results of data analysis with a significance level of 5% was obtained: (1) There is effect of Team Accelerated Instruction (TAI) learning model and Two Stay Two Stray (TSTS) learning model towards mathematics learning achievement, (2) There is effect of learning motivation of students towards mathematics learning achievement, (3) There is no interaction between Team Accelerated Instruction (TAI) learning model and Two Stay Two Stray (TSTS) learning model viewed from learning motivation of students towards mathematics learning achievement. Keyword: Two Stay Two Stray, Team Accelerated Instruction, Learning Motivation, Mathematics Achievement.